The Effect Of Jasmine Aromatherapy on Sleep Quality Among Pre-Menopausal Women in The Working Area of Sukorame Public Health Center - Dwi Sukma Fitriani; Ririn Indriani; Eny Sendra; Indah Rahmaningtyas (Gayaku Publisher, 2026)
Introduction: Sleep quality disturbances are among the common complaints experienced by pre-menopausal women due to hormonal changes occurring during the transition to menopause. Jasmine aromatherapy is known to have a relaxing effect through stimulation of the olfactory and limbic systems, thereby potentially improving sleep quality. Method: This study employed a Pre-Experimental One Group Pretest-Posttest Design. A total of 44 pre-menopausal women were selected using cluster sampling techniques. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Participants received jasmine aromatherapy intervention for five consecutive days. Results: The results of the Wilcoxon Signed Rank Test showed a p-value = 0.000 (p < 0.05) with an effect size (r) of 0.594 which is included in the large effect category. Conclusion: There is a significant effect of Jasmine Aromatherapy on the sleep quality of pre-menopausal women. Jasmine aromatherapy can be used as a complementary non-pharmacological therapy to improve sleep quality among pre-menopausal women.